2020
DOI: 10.1002/vms3.421
|View full text |Cite
|
Sign up to set email alerts
|

Two co‐inherited novel SNPs in the MC4R gene related to live body weight and hormonal assays in Awassi and Arabi sheep breeds of Iraq

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The growth trait of sheep is strived in the breeding program to obtain the heavy body weights within a certain time [1]. The current condition of sheep production in Indonesia is starting to decline due to low genetic quality and production efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth trait of sheep is strived in the breeding program to obtain the heavy body weights within a certain time [1]. The current condition of sheep production in Indonesia is starting to decline due to low genetic quality and production efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The CDS of the ovine MC4R [6]. Several studies have demonstrated that genetic variation in the MC4R gene may affect growth traits in various livestock commodities, including cattle [4], chickens [7], goats [8], and local sheep in the world [1][2][3]. The utilization of the MC4R gene as marker genetic expected could enhance breeding selection and echieve sustainability in lamb meat production, whose demand is increasing yearly.…”
Section: Introductionmentioning
confidence: 99%